Minocycline treatment ameliorates interferon-alpha- induced neurogenic defects and depression-like behaviors in mice - Zheng, Lian-Shun; Kaneko, Naoko; Sawamoto, Kazunobu (Frontiers in Cellular Neuroscience, 2015)
Interferon-alpha (IFN-α) is a proinflammatory cytokine that is widely used for the treatment of chronic viral hepatitis and malignancy, because of its immune-activating, antiviral, and antiproliferative properties. However, long-term IFN-α treatment frequently causes depression, which limits its clinical utility. The precise molecular and cellular mechanisms of IFN-α-induced depression are not currently understood. Neural stem cells (NSCs) in the hippocampus continuously generate new neurons, and some evidence suggests that decreased neurogenesis plays a role in the neuropathology of depression. We previously reported that IFN-α treatment suppressed hippocampal neurogenesis and induced depression-like behaviors via its receptors in the brain in adult mice. However, it is unclear how systemic IFN-α administration induces IFN-α signaling in the hippocampus. In this study, we analyzed the role of microglia, immune cells in the brain, in mediating the IFN-α-induced neurogenic defects and depressive behaviors. In vitro studies demonstrated that IFN-α treatment induced the secretion of endogenous IFN-α from microglia, which suppressed NSC proliferation. In vivo treatment of adult mice with IFN-α for five weeks increased the production of proinflammatory cytokines, including IFN-α, and reduced neurogenesis in the hippocampus. Both effects were prevented by simultaneous treatment with minocycline, an inhibitor of microglial activation. Furthermore, minocycline treatment significantly suppressed IFN-α-induced depressive behaviors in mice. These results suggest that microglial activation plays a critical role in the development of IFN-α-induced depression, and that minocycline is a promising drug for the treatment of IFN-α-induced depression in patients, especially those who are low responders to conventional antidepressant treatments.